Penerapan Model Direct Instruction Pada Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Menulis Karangan di Kelas IV SDN Bintau - Marentek, Risal M.; Kolopita, Windi; Rindengan, Mersty E. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out how the Direct Instruction model is used to improve Narrative essay writing skills in class IV students at SDN Bintau. One of the problems faced is that students still have difficulty writing narrative essays. This is because teachers do not guide students enough in compiling narrative essays, and do not use innovative learning models. This researcher used the Class Action Method (PTK) which consists of Planning, Implementation, Observation, Reflection. The research subjects were fourth grade students at SDN Bintau. Data analysis techniques are written tests and observations. This research was carried out in two cycles. The research results show that the application of the direct instruction model can improve narrative essay writing skills in fourth grade students at SDN Bintau. The increase in students' attitudes/activity during the learning process of narrative essay writing skills increased from the initial condition of being in the poor category, in cycle II to being in the good category. The increase in the average value of narrative essay writing skills in cycle I was 62.85% and in cycle II it increased by 91.42%. It can be concluded that the application of the Direct Instruction model can improve Narrative Essay Writing Skills in class IV students at SDN Bintau.